Information System for the Burial Ground Reservation in the Lendang Guar Narmada Cemetery: Sistem Informasi Pemesanan Tanah Makam di Pemakaman Lendang Guar Narmada - Mulyodiputro, M. Dermawan (SainsTech Innovation Journal, 2019)
Lendang Guar Cemetery is one of the tombs on the island of Lombok in the District of Narmada. At present Lendang Guar tomb management system is still done manually, if a family member dies, they must come to the tomb to fill out the registration form, then choose the location of the tomb. Grave officers have difficulty in collecting data on bodies, heirs, graves that have been filled and the rental price of graves for each block. The tomb clerk also had difficulty in informing the public about the funeral, as well as the heirs whose rental period had ended. Therefore we need information on the ordering of grave land at Lendang Guar Cemetery which can help tomb officers in the management of the cemetery so as to improve services to the community. The research method is done by the waterfall method. The construction of burial ground reservation information system is carried out using the Java programming language with object-oriented programming methods. The menus produced include: inheritance menu, corpse menu, grave block menu, transaction menu, archive extension menu, and report menu.